2019
DOI: 10.1177/1524838019843197
|View full text |Cite
|
Sign up to set email alerts
|

Animal Abuse as a Type of Trauma: Lessons for Human and Animal Service Professionals

Abstract: Animal abuse frequently occurs at the same time and the same place as other types of violence, particularly family violence. Because of that close association, this article proposes that it is the responsibility of both animal service and human service professionals to be aware of its occurrence, understand its significance, and promote appropriate professional and policy responses to it. Research literature addressing the link between animal abuse and other forms of violence (“the link”) is discussed. Article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 50 publications
0
26
0
4
Order By: Relevance
“…The de facto educational policy and resources by government agencies therefore appear to be at odds with those mandated by the Ministry of Education. This is problematic given that there is a well-established link between children abusing animals and becoming abusers of human and nonhuman animals as adults (Flynn 2011;Randour et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The de facto educational policy and resources by government agencies therefore appear to be at odds with those mandated by the Ministry of Education. This is problematic given that there is a well-established link between children abusing animals and becoming abusers of human and nonhuman animals as adults (Flynn 2011;Randour et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Seeing peers abuse animals was the strongest predictor for later animal abuse, followed by seeing parents abuse animals. Randour et al (2019) summarise studies showing how the ages at which children witness animal abuse is correlated with the age at which they become animal abusers themselves. There was a stronger relationship between witnessing animal abuse and becoming an animal abuser if the abuse was witnessed more than once, or if the individual abusing animals in front of the child was a friend, relative, parent or sibling (Gullone 2014;Randour et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Both international and national studies have identified that animals are commonly harmed or killed as a form of family violence and a significant number of women and their children remain in abusive relationships due to concerns for the safety of their pets/animals (Bright et al, 2018;Haden et al, 2018;Roguksi, 2012;Williams et al, 2008). Recognition of this link between animal abuse and family violence has led to a call for greater awareness, and for more interprofessional training, education and cross-referral between human and animal welfare professionals (Holcombe et al, 2016;Newland et al, 2019;Randour et al, 2019;Strand et al, 2012;Williams et al, 2008). Despite the prolific research correlating interpersonal violence, family violence, and child and adult animal cruelty mentioned, challenges for cross-sector reporting are still hindered by the separation of animal and human welfare when it comes to intervention (Long et al, 2007).…”
Section: Viewpoint the Link Between Animal Abuse And Family Violencementioning
confidence: 99%
“…Veterinarians have been identified as potential frontline professionals to recognise and intervene in animal abuse and family violence (Newland et al, 2019;Randour et al, 2019) but they will need to have greater access to resources and continuing education to build confidence in dealing with animal abuse and its association with family violence. Recent research has advocated for ongoing cooperation, coordination, cross-training and consultation between human service and animal service professionals (Randour et al, 2019). Interprofessional collaborations are bolstered through the ability of social workers and academics to analyse, develop and utilise their collaborative skills to empower interprofessional teams.…”
Section: Viewpointmentioning
confidence: 99%
“…The tenets of the Glansville et al (2020) model corroborated previous studies addressing non-compliant pet owners [ 40 ] who do not provide regular and good quality care for their pets. These owners engage in active pet cruelty [ 41 , 42 , 43 ] and passive cruelty, such as failing to provide physical activity, regular feed, grooming and veterinary visits [ 44 ].…”
Section: Introductionmentioning
confidence: 99%